Função polinomial do 1º grau: uma proposta pedagógica por meio de uma UEPS contextualizada com o tema biodíse - Gonçalves, Emanueli Decezaro (2023)
Taking into account that technology has advanced in such a way that it can be used in favor of education, as it is present in the daily lives of students, it is up to the teacher to make this tool an ally in teaching Mathematics. Following this bias, it is increasingly necessary to involve technologies in the teaching and learning process, providing the necessary conditions and elements for Mathematics teachers to be able to promote and facilitate meaningful student learning. In this sense, it is believed that it is possible to work on Mathematics content provided for in the National Common Curricular Base in a more attractive, interactive and contextualized way, opening alternatives to think about a teaching proposal that establishes a relationship in the daily mathematical experience of each student. For the purposes of contextualizing the content of mathematical functions, the topic biodiesel was chosen because it is a fuel from a renewable source present in the region due to the industries installed here and, also, due to the difficulty students have in associating this mathematical content with their everyday. Based on what was mentioned, this research is guided by the question: how can the functions content, contextualized with the biodiesel theme, contribute to more meaningful mathematics teaching? In order to answer this question, the general objective of the present study is to develop, apply and evaluate a Potentially Significant Teaching Unit (UEPS), mediated by digital technologies, for the study of mathematical functions, contextualized through the theme of biodiesel . To implement the UEPS, 16 face-to-face periods were necessary, with 21 students in the ninth year of elementary school from a state public school located in the interior of Rio Grande do Sul. To investigate the relevance of the UEPS, a qualitative research was developed, adopting instruments for data collection such as diagnostic assessment, questionnaires, logbook of the research teacher and materials made by students during the implementation of the didactic proposal were used. It was observed that the results identified UEPS as a good way to provide students with more dynamic, interesting and attractive classes, thus qualifying the teaching and learning process. The educational product linked to this dissertation is a UEPS organized in the form of support material for elementary school Mathematics teachers that addresses the content of mathematical functions contextualized through the theme of biodiesel.